Reducing land take between ambition and reality. The role of actors and instruments in village renewal processes - Ritzinger, Anne (Raumforschung und Raumordnung | Spatial Research and Planning, 2018)
Using the example of the Bavarian Village Renewal Programme, the article investigates which steps and instruments of the village renewal process are capable of steering actors towards a reduction of land take. Two case studies featuring different settlement pressures are analysed using methods of qualitative empirical social research. The continuing transformation of open spaces to built-up areas for settlement and transport is one of the core environmental and planning-related challenges of our time. The reduction of land take is a normative as well as a strategic goal. Particularly in rural areas, however, the divide between land take and population development continues to grow. This phenomenon is the result of decision-making processes of local and regional actors, who are actively zoning out new plots at low prices e.g. in order to achieve a competitive advantage in the intermunicipal struggle for residents and enterprises. Village renewal under the framework of the Federal Land Consolidation Act provides a broad range of instruments, including participation of local actors and landowners, expertise and planning concepts as well as funding and implementation of measures, among others through land readjustment. The article illustrates that while village-renewal processes provide various opportunities to reduce land take and to promote inner development, the objective to reduce land take is not incorporated in the instruments or existing instruments are not fully utilised to that end. The contrasting case studies illustrate how demographic, economic and institutional framework conditions are affecting the actors’ scope of action and rational. The aim of reducing land take is an aim that is desirable from a political and societal perspective. Yet when being weighed against other aims these perspectives often succumb to personal or political interests or to perspectives linked to the process of planning. Finally recommendations for the practice of village renewal and an outlook on future needs of research are given.